Tinjauan dan Pelaksanaan Penyusutan Rekam Medis Di RSU Madani Medan - Lisa Anggriani Tanjung; Siddik Karo-Karo; Indah Fitri Hartanti (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
Depreciation of medical record documents is an activity to separate documents that are declared active and inactive. If the implementation of depreciation is delayed, there will be a buildup of medical record documents that fill the medical record document storage rack. The accumulation of medical record documents makes storage shelves untidy and prone to misplacement of medical record documents (missfile). In Permenkes No. 269/MENKES/PERIII/2008 concerning medical records, medical records are files containing notes and documents regarding patient identity, examination, treatment, actions and other services provided to patients. The purpose of this study was to determine the implementation of shrinking medical record files at Madani Hospital Medan. This type of research is descriptive qualitative. This method is used to describe the cause of the non-implementation of shrinkage of medical record files at RSU Madani Medan. Collecting data in this study conducted interviews with medical record officers. Based on the results of research at Madani General Hospital in Medan, there were 6 medical record officers and only 4 people with RMIK D-III educational background. The implementation of sorting medical record files at RSU Madani Medan is not in accordance with standard operating procedures because the sorting process is more than 5 years old. Hospitals should provide training for filing officers. For non-medical record officers, medical record education and health information to better understand the implementation of depreciation. Hospitals also need to immediately make a retention schedule so that there is a regular schedule for retention.